Alkaline system urea oxidation catalyst and preparation method thereof

By introducing sulfur into the nickel-based catalyst, Ni-Ni3S2 composite catalyst was prepared, which solved the problem of insufficient catalytic activity of the urea oxidation reaction, and achieved efficient urea oxidation reaction, which was suitable for industrial applications of direct urea fuel cells.

CN119581585APending Publication Date: 2025-03-07ZHONGBEI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411426577.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the prior art, the catalytic activity of the urea oxidation reaction (UOR) catalyst is insufficient, resulting in low efficiency of electrocatalytic oxidation of urea and difficult to achieve industrial application.

Method used

By introducing sulfur into the nickel-based catalyst, the electronic structure of the catalyst is regulated, and the Ni-Ni3S2 composite catalyst is prepared for urea oxidation reaction under an alkaline system.

Benefits of technology

It improves the catalytic activity and conductivity of the catalyst, significantly improves the rate and efficiency of the urea oxidation reaction, can replace traditional precious metal catalysts, and is suitable for direct urea fuel cell anode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581585A_ABST
    Figure CN119581585A_ABST
Patent Text Reader

Abstract

The invention relates to an alkaline system urea oxidation catalyst, which is a Ni-Ni3S2 composite catalyst obtained by adding a sulfur salt into a mixed solution of raw materials of nickel salt, urea and melamine for preparing a nickel-based catalyst, preparing a catalyst precursor by a hydrothermal method, and calcining at a high temperature of 550-650 DEG C in an inert atmosphere. The second element sulfur is introduced into the nickel-based catalyst, the electronic structure of the catalyst is changed, the conductivity of the catalyst is improved, and charge transfer in the catalysis process is promoted, so that the reaction rate is increased, and the catalytic activity of the Ni-Ni3S2 composite catalyst is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical catalytic oxidation and relates to a fuel cell anode catalyst, in particular to a direct urea fuel cell anode catalyst in an alkaline system and a preparation method thereof. Background Art

[0002] Hydrogen has the characteristics of wide source, cleanness and high energy density, and is considered to be a sustainable energy source to replace traditional fossil fuels.

[0003] There are many ways to produce hydrogen. Water electrolysis driven by renewable energy has attracted people's attention because it is green and pollution-free. The water electrolysis reaction is divided into the anode oxygen evolution reaction (OER) and the cathode hydrogen evolution reaction (HER). Among them, the higher theoretical potential of OER (1.23V vs RHE) causes problems such as high hydrogen production costs. Therefore, looking for reactions with low oxidation potentials, such as urea oxidation reaction (UOR), methanol oxidation reaction (MOR), hydrazine hydrate oxidation reaction (HzOR), ethanol oxidation reaction (EOR), etc. to replace OER has become a suitable choice for water electrolysis to produce hydrogen. Among them, the theoretical potential of UOR is much lower than that of OER (0.37V vs RHE), and urea has the advantages of wide sources and high hydrogen content (6.67wt%), which has attracted more and more attention from researchers.

[0004] UOR can not only act as the anode reaction of water electrolysis to reduce energy consumption, but also can be used to treat urea pollution and play a role in cleaning the environment. The electrocatalytic oxidation reaction process of urea in alkaline medium is shown as follows: Anode: CO ( NH 2)2 + 6 OH - →N 2 ↑ + 5 H 2 O+CO 2↑ + 6 e - (1) Cathode: 6 H 2 O+ 6 e - → 3 H 2↑ + 6 OH - (2) Overall: CO ( NH 2)2 + 6 OH- →N 2 ↑ + 3 H 2↑ +CO 2↑ (3)

[0005] As can be seen from the formula, UOR is a six-electron transfer reaction, which means that the reaction kinetics of UOR is limited, hindering the practical application of UOR. Therefore, it is necessary to develop efficient catalysts to improve the catalytic performance of urea (Modulating the electronic structure of Ni(OH)2 by coupling with low-content Pt for boostingthe urea oxidation reaction enables significantly promoted energy-savinghydrogen production. Energy&Environmental Science. 2024; 17: 1984-96.).

[0006] Precious metals such as Pt, Ru and Ir and their complexes are often used as highly active catalysts for UOR. However, the high cost and scarcity of precious metals limit their widespread application in actual production. In order to realize the industrialization of urea electrocatalytic oxidation, people have shifted their research focus to transition metal catalysts, which are abundant and inexpensive.

[0007] Wang D et al. (Electrochemically reduced graphene oxide–nickelnanocomposites for urea electrolysis. Electrochimica Acta. 2013;89:732-6.) found that although the transition metal Ni has a high catalytic activity for UOR, the catalytic performance of single metal Ni still cannot meet the demand, and it is necessary to form a complex with other elements to improve the intrinsic electrocatalytic activity and corrosion resistance of the catalyst. Summary of the invention

[0008] The purpose of the present invention is to provide an alkaline system urea oxidation catalyst and a preparation method thereof, by introducing a second element of sulfur into the nickel-based catalyst to regulate the electronic structure of the catalyst, thereby further improving the catalytic activity of the nickel-based catalyst.

[0009] Specifically, the alkaline system urea oxidation catalyst described in the present invention is prepared by adding sulfur salt to a mixed solution of raw materials nickel salt, urea and melamine for preparing a nickel-based catalyst, preparing a catalyst precursor by a hydrothermal method, and calcining at a high temperature of 550 to 650° C. under an inert atmosphere to obtain a Ni-Ni3S2 composite catalyst, wherein the molar ratio of the nickel salt to the sulfur salt is controlled to be 3: (4 to 6).

[0010] More specifically, in the mixed solution of the present invention, the molar ratio of nickel salt to urea and melamine is preferably 3:(2-4):(1-3).

[0011] The nickel salt may be any conventional water-soluble inorganic or organic nickel salt, including but not limited to any one of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate. Furthermore, the present invention preferably uses nickel sulfate.

[0012] The sulfur salt can be a water-soluble sulfur-containing compound such as thiourea, sodium sulfide, thioacetamide, etc. Further, thiourea is preferably used in the present invention.

[0013] The present invention adopts a one-step hydrothermal method and controls the ratio of nickel salt to sulfur salt to prepare a composite catalyst containing Ni and S with a nanosheet structure. The composite catalyst not only provides more active sites for UOR, but also facilitates electrolyte diffusion and has excellent electrochemical reaction activity. The composite catalyst can replace traditional precious metal catalysts in the electrocatalytic oxidation reaction of urea.

[0014] Furthermore, the present invention also provides a method for preparing a suitable alkaline system urea oxidation catalyst, which comprises dissolving the raw materials in water to obtain a mixed solution according to the molar ratio of nickel salt, urea, melamine and sulfur salt of 3:(2-4):(1-3):(4-6), carrying out a hydrothermal reaction at 100-150°C for 5-8h to prepare a catalyst precursor, and then calcining at 550-650°C under an inert atmosphere to obtain a Ni-Ni3S2 composite catalyst.

[0015] Specifically, the present invention preferably calcines the catalyst precursor at high temperature for no less than 2 hours.

[0016] More preferably, the present invention preferably raises the temperature of the catalyst precursor to the calcination temperature at a rate of 2 to 5° C. / min under an inert atmosphere.

[0017] The Ni-Ni3S2 composite catalyst prepared by the present invention can be applied to the anode of a direct urea fuel cell and used as a UOR anode catalyst.

[0018] Based on this, the present invention also provides an anode for a direct urea fuel cell, which is prepared by coating the Ni-Ni3S2 composite catalyst of the present invention on an anode material.

[0019] Specifically, the Ni-Ni3S2 composite catalyst prepared by the present invention is dispersed in an ethanol aqueous solution to form a uniform slurry, which is then coated on a carbon cloth and dried to form a working electrode. The working electrode does not use any adhesive, thereby avoiding the presence of an inactive area and making the working electrode have better conductivity.

[0020] Due to the introduction of sulfur atoms, the electronic structure of the catalyst is changed, the conductivity of the catalyst is improved, and the charge transfer in the catalytic process is promoted, thereby increasing the reaction rate and further improving the catalytic activity of the Ni-Ni3S2 composite catalyst.

[0021] Cyclic voltammetry was used to evaluate the activity of the Ni-Ni3S2 composite catalyst for the electrocatalytic oxidation of urea. In 1.0MKOH+0.33M Urea electrolyte, the peak current density at a voltage of 1.699V at a scan rate of 50mV / s could reach 274.60mA cm -2 , has a significant catalytic effect on urea oxidation. At the same time, at a voltage of 1.6V, after 50h of chronoamperometry test, the current density retention rate was 91.9%, and the catalyst maintained good conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is the X-ray diffraction pattern of the composite catalyst prepared in Example 1 and Comparative Examples 1-3.

[0023] Figure 2 It is the CV curve of the composite catalyst prepared in Example 1 and Comparative Examples 1 to 3 in 1.0 M KOH solution.

[0024] Figure 3 It is the CV curve of the composite catalyst prepared in Example 1 and Comparative Examples 1-3 in 1.0M KOH+0.33M Urea solution.

[0025] Figure 4 The composite catalysts prepared in Example 1 and Comparative Examples 1 to 3 were -2 The corresponding voltage.

[0026] Figure 5 This is a 50h chronoamperometry IT test chart of the composite catalyst prepared in Example 1. Implementation

[0027] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.

[0028] The production processes, experimental methods or detection methods involved in the embodiments of the present invention, unless otherwise specified, are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the field, and are very clear and unambiguous in the relevant application fields. Technical personnel in the field can understand the conventional process steps based on the names and apply the corresponding equipment, and implement them according to conventional conditions or the conditions recommended by the manufacturer.

[0029] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art. Example

[0030] Example 1

[0031] Weigh 0.87 g of nickel nitrate, 0.18 g of urea, 0.25 g of melamine and 0.30 g of thiourea, add them into a beaker containing 150 mL of deionized water, stir them magnetically in a water bath until dissolved, transfer them to a reactor, heat them to 120 °C in a sealed manner for hydrothermal reaction for 6 h, cool them to room temperature, and filter them to obtain a solid powder.

[0032] The solid powder was collected in a porcelain boat, placed in a tubular furnace, and heated to 600°C at a rate of 2°C / min under the condition of continuous nitrogen flow, and heated at a constant temperature for 2h to obtain a Ni-Ni3S2 catalyst.

[0033] Example 2

[0034] Weigh 0.87 g of nickel nitrate, 0.12 g of urea, 0.12 g of melamine and 0.38 g of thiourea, add them into a beaker containing 150 mL of deionized water, stir them magnetically in a water bath until dissolved, transfer them to a reactor, heat them to 110°C in a sealed manner for hydrothermal reaction for 5 h, cool them to room temperature, and filter them to obtain a solid powder.

[0035] The solid powder was collected in a porcelain boat, placed in a tube furnace, and heated to 550°C at a rate of 2°C / min under the condition of continuous nitrogen flow, and heated at a constant temperature for 2.1h to obtain a Ni-Ni3S2 catalyst.

[0036] Example 3

[0037] Weigh 0.87 g of nickel nitrate, 0.24 g of urea, 0.38 g of melamine and 0.46 g of thiourea, add them into a beaker containing 150 mL of deionized water, stir them magnetically in a water bath until dissolved, transfer them to a reactor, heat them to 130 °C in a sealed manner for hydrothermal reaction for 7 h, cool them to room temperature, and filter them to obtain a solid powder.

[0038] The solid powder was collected in a porcelain boat, placed in a tubular furnace, and heated to 650°C at a rate of 2°C / min under continuous nitrogen flow, and heated at a constant temperature for 2.2 h to obtain a Ni-Ni3S2 catalyst.

[0039] Comparative Example 1

[0040] Weigh 0.87 g of nickel nitrate, 0.18 g of urea and 0.25 g of melamine, add them into a beaker containing 150 mL of deionized water, stir them magnetically in a water bath until dissolved, transfer them to a reactor, heat them to 120° C. in a sealed container for hydrothermal reaction for 6 h, cool them to room temperature, and filter them to obtain a solid powder.

[0041] The solid powder was collected in a porcelain boat, placed in a tube furnace, and heated to 600°C at a rate of 2°C / min under the condition of continuous nitrogen flow, and heated at a constant temperature for 2h to obtain a Ni-NiO catalyst.

[0042] Comparative Example 2

[0043] Weigh 0.87 g of nickel nitrate, 0.18 g of urea, 0.25 g of melamine and 0.15 g of thiourea, add them into a beaker containing 150 mL of deionized water, stir them magnetically in a water bath until dissolved, transfer them to a reactor, heat them to 120 °C in a sealed manner for hydrothermal reaction for 6 h, cool them to room temperature, and filter them to obtain a solid powder.

[0044] The solid powder was collected in a porcelain boat, placed in a tubular furnace, and heated to 600°C at a rate of 2°C / min under continuous nitrogen flow, and heated at a constant temperature for 2h to obtain a Ni / NiO-Ni3S2 catalyst.

[0045] Comparative Example 3

[0046] Weigh 0.87 g of nickel nitrate, 0.18 g of urea, 0.25 g of melamine and 0.53 g of thiourea, add them into a beaker containing 150 mL of deionized water, stir them magnetically in a water bath until dissolved, transfer them to a reactor, heat them to 120°C in a sealed state for hydrothermal reaction for 6 h, cool them to room temperature, and filter them to obtain a solid powder.

[0047] The solid powder was collected in a porcelain boat, placed in a tubular furnace, and heated to 600°C at a rate of 2°C / min under the condition of continuous nitrogen flow, and heated at a constant temperature for 2h to obtain a Ni3S2 catalyst.

[0048] Figure 1First, the standard X-ray diffraction spectra of single components Ni, NiO and Ni3S2 are provided, among which the diffraction peaks at 44.4°, 51.8° and 76.3° correspond to the (111), (200) and (220) crystal planes of Ni, respectively (PDF#87-0712); the diffraction peaks at 37.2°, 43.2° and 62.8° correspond to the (111), (200) and (220) crystal planes of NiO, respectively (PDF#78-0423); the diffraction peaks at 21.7°, 31.10°, 37.78°, 44.3°, 50.12° and 55.16° correspond to the (101), (110), (003), (202), (211) and (122) crystal planes of Ni3S2, respectively (PDF#44-1418).

[0049] Figure 1 X-ray diffraction patterns of catalysts prepared in Example 1 and Comparative Examples 1 to 3 are also provided, and compared with standard spectra of Ni, NiO and Ni3S2, proving that Example 1 successfully prepared Ni-Ni3S2 catalysts, which only contain active components Ni and Ni3S2. However, it can be seen from the comparison that there are only two active components, Ni and NiO, in the catalyst of Comparative Example 1, three active components, Ni, NiO and Ni3S2, in the catalyst of Comparative Example 2, and only one active component, Ni3S2, in the catalyst of Comparative Example 3, which proves that the change in the ratio of nickel salt to sulfur salt directly affects the formation of the catalyst, and thus has a certain influence on the performance of the catalyst. The catalyst of Example 1 fully exerts its effects through the two active components Ni and Ni3S2, providing the best UOR catalytic activity.

[0050] Application Example 1

[0051] 5.0 mg of Ni-Ni3S2, Ni / NiO, Ni / NiO-Ni3S2 and Ni3S2 catalysts prepared in the above embodiments and comparative examples were weighed respectively, dispersed in a mixed solution consisting of 30 μL of deionized water and 30 μL of anhydrous ethanol, ultrasonicated for 10 min to form a uniform slurry, applied on a carbon cloth of 0.5 cm×1.5 cm, and dried.

[0052] The electrochemical properties of different catalysts were characterized by cyclic voltammetry (CV) using a three-electrode system, with carbon cloth coated with different catalysts as the working electrode, a 3.0 cm × 4.0 cm stainless steel sheet as the counter electrode, and a mercury oxide electrode as the reference electrode.

[0053] 1.0 M KOH and 1.0 M KOH + 0.33 M Urea solution were used as electrolyte solutions, respectively. Shanghai Chenhua CHI660E electrochemical workstation was used to conduct the electrochemical test at a voltage of -0.055 to 0.745 V at a speed of 50 mVs -1The urea electrochemical oxidation (UOR) reaction activity was tested at a scan rate of .

[0054] exist Figure 2 In the 1.0 M KOH electrolyte solution, although the four catalysts have different active components, redox peaks appear. The peak in the voltage range of 1.4 to 1.6 V corresponds to Ni 2+ To You 3+ The oxidation peak in the voltage range of 1.2 to 1.4 V corresponds to Ni 3+ To You 2+ Among the four catalysts, Ni-Ni3S2 has the largest closed area and the highest peak current density, which is greater than Ni / NiO-Ni3S2, Ni / NiO and Ni3S2, indicating that Ni-Ni3S2 has the largest specific capacitance.

[0055] In addition, Ni in Ni-Ni3S2 2+ To You 3+ The oxidation potential is the lowest and the anodic peak is the highest, indicating that NiOOH is enriched on the catalyst surface, the electrochemical activity is the best, and it is more conducive to the UOR catalytic reaction.

[0056] Figure 3 When 0.33 M Urea was added to 1.0 M KOH electrolyte, the current density of the catalysts increased to varying degrees, indicating that all catalysts have catalytic activity for UOR, but the activity varies. Among them, the current density of the Ni-Ni3S2 composite catalyst is 274.60 mA cm -2 Significantly higher than Ni / NiO-Ni3S2 (218.12 mA cm -2 )、Ni / NiO(189.64mA cm -2 ) and Ni3S2 (139.72 mA cm -2 ).

[0057] At the same time, from Figure 4 It can also be seen that at 10 mA cm -2 At the same current density, the potential of the Ni-Ni3S2 composite catalyst for UOR is 1.3642 V (pH 13.8), which is also significantly lower than Ni / NiO-Ni3S2 (1.3759 V), Ni / NiO (1.3762 V) and Ni3S2 (1.3788 V), indicating that Ni-Ni3S2 has extremely high catalytic activity for UOR.

[0058] The CA test of Ni-Ni3S2 composite catalyst was carried out at a voltage of 1.435V. Figure 5It can be seen that after 50h of CA test, the current density of Ni-Ni3S2 increased from 111.68mA cm -2 Down to 102.68 mA cm -2 , the retention rate is 91.9%. Considering the stability, Ni-Ni3S2 still maintains the best performance.

[0059] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.

Claims

1. An alkaline system urea oxidation catalyst is prepared by adding sulfur salt to a mixed solution of raw materials nickel salt, urea and melamine for preparing a nickel-based catalyst, preparing a catalyst precursor by a hydrothermal method, and calcining at 550-650° C. under an inert atmosphere to obtain a Ni-Ni3S2 composite catalyst, wherein the molar ratio of the nickel salt to the sulfur salt is controlled to be 3:(4-6).

2. The alkaline system urea oxidation catalyst according to claim 1, characterized in that The molar ratio of nickel salt to urea and melamine is 3:(2-4):(1-3).

3. The alkaline system urea oxidation catalyst according to claim 1, characterized in that The nickel salt is any one of water-soluble inorganic or organic nickel salts such as nickel sulfate, nickel nitrate, nickel chloride or nickel acetate.

4. The alkaline system urea oxidation catalyst according to claim 3, characterized in that The nickel salt is nickel sulfate.

5. The alkaline system urea oxidation catalyst according to claim 1, characterized in that The sulfur salt is any one of the water-soluble sulfur-containing compounds thiourea, sodium sulfide or thioacetamide.

6. The alkaline system urea oxidation catalyst according to claim 5, characterized in that The thionium salt is thiourea.

7. The method for preparing the alkaline system urea oxidation catalyst according to claim 1 is to dissolve nickel salt, urea, melamine and sulfur salt in water in a molar ratio of 3:(2-4):(1-3):(4-6) to obtain a mixed solution, perform hydrothermal reaction at 100-150°C for 5-8h to prepare a catalyst precursor, and then calcine at 550-650°C under an inert atmosphere to prepare a Ni-Ni3S2 composite catalyst.

8. The method for preparing the alkaline system urea oxidation catalyst according to claim 7, characterized in that The catalyst precursor is calcined at high temperature under an inert atmosphere for not less than 2 hours.

9. Use of the alkaline system urea oxidation catalyst according to claim 1 as an anode catalyst for a direct urea fuel cell.

10. An anode for a direct urea fuel cell, wherein the alkaline system urea oxidation catalyst according to claim 1 is coated on an anode material.

Citation Information

Patent Citations

  • Nickel foam loaded nickel sulfide used as urea oxidation catalyst electrode and preparation method thereof

    CN115466980A